Endoscopic exploratory tympanotomy findings in conductive hearing loss: a surgical review - Sanjeev Mohanty; Vinay Raj T; Sreenivas C; Devipriya V (International Journal of Medical Research and Review, 2017)
Background: Conductive hearing loss continue to remain undiagnosed in a large number of patients with intact membrane. Endoscope assisted tympanotomy provides an alternative technique for diagnosis and also facilitates treatment.Methods: A prospective analysis over a 5 year period of 72 exploratory tympanotomies for conductive hearing loss was performed in patients with intact tympanic membrane. Per operative findings were treated in the same sitting. Post-operative follow up of the patient was done up to 6 months.Results: The most common operative diagnosis was found to be otosclerosis (66%), followed by traumatic ossicular dislocation, tympanosclerotic patch, middle ear adhesions, foreign bodies etc. Small fenestra Stapedotomy with prosthesis insertion was the preferred surgical procedure performed in this study, resulting in perceptible hearing improvement post operatively.Conclusion: Endoscope assisted tympanotomy and associated middle ear surgeries serves as an effective diagnostic and therapeutic option. This study is of value in assessing the surgical challenges in diagnosis and definitive treatment for conductive hearing loss with an intact tympanic membrane.